Brachial plexus surgery: the role of the surgical technique for improvement of the functional outcome - Leandro Pretto Flores (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: The study aims to demonstrate the techniques employed in surgery of the brachial plexus that are associated to evidence-based improvement of the functional outcome of these patients. METHOD: A retrospective study of one hundred cases of traumatic brachial plexus injuries. Comparison between the postoperative outcomes associated to some different surgical techniques was demonstrated. RESULTS: The technique of proximal nerve roots grafting was associated to good results in about 70% of the cases. Significantly better outcomes were associated to the Oberlin's procedure and the Sansak's procedure, while the improvement of outcomes associated to phrenic to musculocutaneous nerve and the accessory to suprascapular nerve transfer did not reach statistical significance. Reinnervation of the hand was observed in less than 30% of the cases. CONCLUSION: Brachial plexus surgery renders satisfactory results for reinnervation of the proximal musculature of the upper limb, however the same good outcomes are not usually associated to the reinnervation of the hand.